Molecular epidemiology of plasmid patterns in Shigella flexneri types 1-6. - Gebre-Yohannes, A. (Cambridge University Press, 1991)
A total of 123 drug-resistant and drug-sensitive Shigella flexneri types 1-6, and their Escherichia coli K12 transconjugants were used for plasmid profile analysis by agarose gel electrophoresis. Resistance factors (R-factors) were further characterized by incompatibility testing. The overall distribution of small plasmids in S. flexneri showed that a cryptic plasmid of about 4.6 Kb was found in all serotypes, and a plasmid of about 4.2 Kb was found in serotypes 1-4. Shigella flexneri types 2, 4 and 6 showed a 6.5 Kb plasmid which correlated with SSu-resistance. All S. flexneri serotypes harboured large plasmids of about 217 Kb. Plasmid profile analysis of S. flexneri in Ethiopia showed a high degree of uniformity within individual serotypes. However, there was a limited variability which, at times, could be useful for epidemiological investigation. Shigella flexneri serotypes 1-6 harboured resistance plasmids with diverse molecular weights but mostly belonging to incompatibility groups N and X.